Multi-modal intervention to reduce cardiovascular risk among hypertensive older adults: Design of a randomized clinical trial - Buford, Thomas W. (Contemp Clin Trials, 2015)
Persons aged over 65 years account for over 75% of healthcare expenditures and deaths attributable to cardiovascular disease (CVD). Accordingly, reducing CVD risk among older adults is an important public health priority. Functional status, determined by measures of physical performance, is an important predictor of cardiovascular outcomes in older adults and declines more rapidly in seniors with hypertension. To date, physical exercise is the primary strategy for attenuating declines in functional status. Yet despite the general benefits of training, exercise alone appears to be insufficient for preventing this decline. Thus, alternative or adjuvant strategies are needed to preserve functional status among seniors with hypertension. Prior data suggest that angiotensin converting enzyme inhibitors (ACEi) may be efficacious in enhancing exercise-derived improvements in functional status yet this hypothesis has not been tested in a randomized controlled trial. The objective of this randomized, double-masked pilot trial is to gather preliminary efficacy and safety data necessary for conducting a full-scale trial to test this hypothesis. Sedentary men and women ≥ 65 years of age with functional limitations and hypertension are being recruited into this 24 week intervention study. Participants are randomly assigned to one of three conditions: (1) ACEi plus exercise training, (2) thiazide diuretic plus exercise training, or (3) AT1 receptor antagonist plus exercise training. The primary outcome is change in walking speed and secondary outcomes consist of other indices of CV risk including exercise capacity, body composition, as well as circulating indices of metabolism, inflammation and oxidative stress.